Perancangan Aplikasi Pembelajaran Bahasa Inggris Dengan Chatbot dan Ruang Diskusi - Tiowardhana, Alvin; Afandi, Mohamad Irwan; Wibowo, Nur Cahyo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Autonomous learning plays an important role in online learning, especially in multicultural environments such as Little Sun School which teaches English, Mandarin and Indonesian language learning. However, the use of WhatsApp application as a communication medium is considered ineffective to support discussion and question and answer in autonomous learning. Therefore, this research develops an Android-based chatbot application using a rule-based method that is able to provide automatic responses and provide a private discussion space between students and teachers. This application is developed using waterfall method and utilizes Firebase for user authentication, real-time data storage, and file management. Interim trials showed that the Chat Lang app can provide quick and structured responses, increase student participation, speed up the question and answer process, and improve interaction between students and teachers, compared to previous communication methods. These results indicate that the Chat Lang app is effective in supporting self-directed learning.